GAMBARAN GANGGUAN MUSKULOSKELETAL PADA AREA LUTUT PADA GURU DI DAERAH JABODETABEK - Luthfiyah G, (2021)
Musculoskeletal disorders (MSD) can still occur in teachers during stay at home activities during WFH, one of which is knee pain that can interfere with daily activities. Factors such as gender, age, BMI, years of service, ergonomics were associated with a higher prevalence of MSDs among teachers. The purpose of this study was to examine the description of musculoskeletal disorders in the knee in school teachers in the Jabodetabek area. The research design used is descriptive quantitative with a cross sectional approach. The population in this study are school teachers in Jabodetabek. Obtained a sample of 325 teachers who met the inclusion and exclusion criteria. In the results of the study, there were 75 teachers (23.1%) who experienced musculoskeletal complaints in the knee area, while 250 teachers (76.9%) did not experience knee complaints. Most of the teachers who experienced this disorder were female teachers (81.3%) with the highest age percentage at 32% and included in the obesity category 1 (34.7%). The majority of teachers who experience knee complaints have worked for > 15 years (50.7%) with a work duration of 4-5 hours (38.7%) during the pandemic. Most of the teachers spent less than 3 hours sitting (58.7%) while teaching and < 10 minutes (38.7%) for standing. Of the 75 teachers who have complaints, as many as 29 teachers (38.7%) have implemented an ergonomic position when teaching. The conclusion of this study is that there are musculoskeletal disorders that occur in the knee with a percentage of 23.1% and several factors that are closely related to these complaints.